Adhesive restoration in posterior teeth using semidirect technique - da Silva Júnior, Maciel E. [UNESP]; Ohata, Gabriela [UNESP]; Tonetto, Mateus R.; de Campos, Edson A. [UNESP]; de Andrade, Marcelo F. [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Aim: The aim of this article was to present a detailed case report of semidirect composite restoration in tooth #36 and its anatomical and esthetic reestablishments. Semidirect restorative technique is an alternative with many advantages for both clinicians and patients. It can improve esthetics with minimal dental tissue removal, reduce polymerization contraction, improve marginal sealing, reduce infiltration and postoperative sensitivity, and enhance the restoration longevity. Moreover, it is a low-cost technique and carried out in a single session. A female patient reported with sensitivity and discomfort in tooth #36 region; clinical evaluation showed marginal infiltration and restoration loss, and thus, semidirect restoration technique was recommended. The impression was carried out using precision alginate, and a semirigid addition silicone model was obtained. Semidirect restoration was performed using a model outside the mouth. Semidirect restoration is a viable alternative improving dental esthetics with conservative treatment, reducing polymerization shrinkage, improving marginal sealing, reducing infiltration and postoperative sensitivity, and enhancing restoration quality. Clinical significance: Semidirect restoration is a low-cost technique with advantages, such as polymerization control, esthetic refinement, and facilitating of occlusal and contact point adjustments.
Keywords: Dental esthetics; Esthetic dentistry; Indirect-direct restoration